MECHANISMS FOR PROTECTION AGAINST ATTACKS IN WEB SYSTEMS - Ibrokhimov A.R. (The Conference Hub, 2025)
The main information security threats encountered in the framework of modern web systems architecture and effective protection mechanisms against them are analyzed. With the widespread popularity of web applications, the issue of ensuring their security level has become one of the pressing problems. The article examines the main mechanisms used to increase the level of protection of web applications, including firewalls, IDS, IPS systems, SSL/TLS protocols, web application firewalls, access control, security monitoring and incident response systems.
Keywords: firewall , IDPS , SSL/TLS , WAF , XSS, SQL injection, access control, Security patching and updating, Security monitoring and incident response.